Protein Loosing Enteropathy Secondary to Strongyloidiasis: Case Report and Review of the Literature - Weam El Hajj; Gilbert Nakad; Antoine Abou Rached (Case Reports in Gastrointestinal Medicine)
Strongyloidiasis is a helminthic disease which affects millions around the world resulting in a significant burden in certain high risk groups. It is rarely reported in the Lebanese population probably due to the low index of suspicion in common practice. We are reporting a case of strongyloidiasis that was found in an elderly patient presenting initially with dyspnea followed by skin rash, protein loosing enteropathy, diarrhea, and abdominal pain while on corticosteroid therapy. The diagnosis was suspected based on clinical presentation in addition to peripheral eosinophilia. We will also describe the upper and lower endoscopic aspects of the disease, as well as histologic findings on duodenal and colonic biopsies.